An Ant Colony System for Solving DNA Sequence Design Problem in DNA Computing - Farhaana, Yakop; Zuwairie, Ibrahim; Amar Faiz, Zainal Abidin; Zulkifli, Md. Yusof; Mohd Saberi, Mohamad; Khairunizam, Wan; Watada, Junzo (ICIC International, 2013)
Link to publisher's homepage at http://www.ijicic.org/